#TITLE_ALTERNATIVE# - ADYASARI (NIM 15306016); Pembimbing: Dr. Ir. Agus Jatnika Effendi, DINI
The azo dye is the main problem of the waste produced by the textile industries. It is very dangerous to living entities due to its toxicity and mutagenic properties. In order to remove the properties (color) of the azo dye waste when disposing to the water environment, this research developed a new concept using a Biology Treatment Process called as a membrane bioreactor (BRM). BRM has three tanks, which is anoxic, contacts, and stabilization, and it operates with various cosubstrate concentrations, namely 2%, 4%, 6%, 8%, and 10%. The purpose of this research is to determine the dynamics of microbial population that affect the engineering process occurs in the BRM, such as azo dyes decolorization and organic matter removal. Parameters being measured are the changes in microbial populations in each tank, the identification of dominant microbial species, and the influence of microbes on color and organic matter removal. Results showed that optimum microbial growth occurred in the co-substrate concentration of 6%. Microbes contribute significantly in azo dyes removal, especially microbes in anoxic tank. There are 7 species identified as dominant species that contribute in the engineering process of BRM.